Post-weaning folate deficiency induces a depression-like state via neuronal immaturity of the dentate gyrus in mice - Shoji Nishida; Ryota Araki; Akihiro Baba; Sota Asari; Shin Tachibana; Yuki Nakajima; Arimi Iwakumo; Takeshi Yabe (Elsevier, 2020)
Folate deficiency has been suggested as a risk factor for depression in preclinical and clinical studies. Several hypotheses of mechanisms underlying folate deficiency-induced depressive symptoms have been proposed, but the detailed mechanisms are still unclear. In this study, we assessed whether post-weaning folate deficiency affect neurological and psychological function. The low folate diet-fed mice showed depression-like behavior in the forced swim test. In contrast, spontaneous locomotor activity, social behavior, coordinated motor skills, anxiety-like behavior and spatial memory did not differ between control and low folate diet-fed mice. In the dentate gyrus (DG) of the hippocampus, decreased number of newborn mature neurons and increased number of immature neurons were observed in low folate diet-fed mice. Staining with Golgi-Cox method revealed that dendritic complexity, spine density and the number of mature spines of neurons were markedly reduced in the DG of low folate diet-fed mice. Stress response of neurons indicated as c-Fos expression was also reduced in the DG of low folate diet-fed mice. These results suggest that reduction in the degree of maturation of newborn hippocampal neurons underlies folate deficiency-induced depressive symptoms.